GenAI in SMEs : Navigating Implementation Challenges in Selected European Contexts - Santoro, Lorenzo; Kania, Karolina Anna; Tkáčik, Marcel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis concentrates on the barriers and challenges small and medium enterprises (SMEs) in the Italian Market face in implementing Generative AI (GenAI) tools. It explores different obstacles (technical, operational, and financial among others) that these businesses encounter, highlighting different approaches to GenAI adoption in SMEs.
Vedoucí práce: Karolina Anna Kania
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses